2013
DOI: 10.1021/jp403066q
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Arenethiolate-Capped PbS Quantum Dots: Optoelectronic Properties, Self-Assembly, and Application in Solution-Cast Photovoltaics

Abstract: Suitable postsynthesis surface modification of lead-chalcogenide quantum dots (QDs) is crucial to enable their integration in photovoltaic devices. Here we exploit arenethiolate anions to completely replace pristine oleate ligands on PbS QDs in the solution phase, thus preserving the colloidal stability of QDs and allowing their solution-based processability into photoconductive thin films. Complete QD surface modification relies on the stronger acidic character of arenethiols compared to that of alkanethiols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
149
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(162 citation statements)
references
References 75 publications
8
149
1
1
Order By: Relevance
“…These can be directly deposited, simplifying the manufacturing, and using materials and solvents more efficiently. [33][34][35] Unfortunately, the highest-performing devices reporetd to date based on this approach have been limited to PCEs of 6%, considerably below the best layer-by-layer CQD devices.Liganding CQDs using methylammonium iodide (MAI) was recently shown to offer the possibility of short-ligand-exchanged CQDs that could be directly deposited from a polar solvent. 20 Very recently, it was reported that PbS quantum dots and methylammonium lead triiodide perovskites (MAPbI 3 ) can exhibit coherence in their lattice fringes owing to their minimal lattice mismatch.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These can be directly deposited, simplifying the manufacturing, and using materials and solvents more efficiently. [33][34][35] Unfortunately, the highest-performing devices reporetd to date based on this approach have been limited to PCEs of 6%, considerably below the best layer-by-layer CQD devices.Liganding CQDs using methylammonium iodide (MAI) was recently shown to offer the possibility of short-ligand-exchanged CQDs that could be directly deposited from a polar solvent. 20 Very recently, it was reported that PbS quantum dots and methylammonium lead triiodide perovskites (MAPbI 3 ) can exhibit coherence in their lattice fringes owing to their minimal lattice mismatch.…”
mentioning
confidence: 99%
“…These can be directly deposited, simplifying the manufacturing, and using materials and solvents more efficiently. [33][34][35] Unfortunately, the highest-performing devices reporetd to date based on this approach have been limited to PCEs of 6%, considerably below the best layer-by-layer CQD devices.…”
mentioning
confidence: 99%
“…Popular ligands for CQD electronic film applications include alkane and aromatic thiols, amines and carboxylic acids [16,85,[93][94][95][96], metal chalcogenide complexes [90] and halogen atoms [97]. Most organic ligands consist of three parts: an inner anchor to the quantum dot, a middle hydrophilic segment and an outer functional group.…”
Section: Ligand Typesmentioning
confidence: 99%
“…Most high-performing devices utilize short thiol ligands [184] in combination with inorganic halide ligands [16], which are delivered through solid-state or solution-phase ligand exchanges. Improved ligand strategies typically lower the density of mid-gap electronic trap states while increasing diffusion lengths and carrier mobilities [16,95,134,135,185]. The highest certified PCE to date of 9.9% has been achieved in a modified DH architecture [102].…”
Section: Depleted Heterojunction Cqd Photovoltaicsmentioning
confidence: 99%
“…Sustained interests in colloidal lead chalcogenide, PbX (X¼S, Se, Te), nanocrystals (NCs) arise from the materials' large exciton Bohr radius, high molar absorption coefficients, small effective masses of charge carriers, and tunable interparticle spacing and morphology, which translate to suitability in photovoltaic and optoelectronic applications [1,2]. Synthesis of tailored NCs via solution chemistry routes with high accuracy and precision have been achieved by systematic control of thermodynamic parameters and growth kinetics, with the aid of careful selection of precursors, solvents, capping agents and catalysts [3][4][5].…”
Section: Introductionmentioning
confidence: 99%